Surgical and Audiologic Outcomes in Endoscopic Stapes Surgery across 4 Institutions. (22nd March 2016) - Hunter, Jacob B.; Zuniga, M. Geraldine; Leite, Janaina; Killeen, Daniel; Wick, Cameron; Ramirez, Julian; Rivas, Jose A.; Nogueira, Joao F.; Isaacson, Brandon; Rivas, Alejandro
Abstract : Objectives: To investigate intra‐ and postoperative outcomes of endoscopic stapes surgery. Study Design: Case series with chart review. Setting: Four tertiary care otologic centers. Subjects and Methods: Sixty‐five subjects 18 years and older who underwent endoscopic stapes surgeries were analyzed. Variables analyzed included surgical techniques and intraoperative findings. Outcomes measured included postoperative hearing and complications to date. Results: Fifty‐one patients met inclusion and exclusion criteria. The average patient age was 48.1 years (range, 26‐87 years), with 60.0% female patients. Patients had a median follow‐up of 5.13 months (range, 0.8‐57.4 months). Of the subjects, 71.7% required scutum removal. The chorda tympani nerve was manipulated in 94.0% of subjects and transected in 12.0%. At last follow‐up visit, the median air‐bone gap decreased from 34.5 dB hearing level (HL) preoperatively to 9.0 dB HL postoperatively ( P <. 0001). Ninety percent of subjects had closure of their air‐bone gap ≤20 dB HL. Intraoperative complications included tympanic membrane tears in 8.0% of subjects, all of which resolved at first follow‐up. Postoperatively, 10.0% of subjects complained of altered taste. Conclusions: The present multicentered study of endoscopic stapes surgery demonstrates similar audiometric and postoperative outcomes previously published in the literature, with a median postoperative air‐bone gap of 9.0 dB HL. Future prospective endoscopic stapes surgery studies, addressing the need for scutum removal, postoperative taste changes, and pain scores, are merited.